Determinant of Customer Satisfaction in Using Losari Beach Hotel Makassar Services with Service Quality Variables - Rizka Aisyah Nurjannah; Andi Naila Quin Azisah Alisyahbana; Nursinah Amrullah (Global Research Collaboration, 2023)
This study aims to determine whether the dimensions of service quality, namely tangible, reliability, responsiveness, assurance, and empathy, affect customer satisfaction at Losari Beach Hotel Makassar and analyze the most dominant factor in influencing customer satisfaction at Losari Beach Hotel Makassar. The population in this study were guests staying at Losari Beach Hotel Makassar while the sample taken was 100 respondents using Non-Probability Sampling technique with Accidental sampling approach, which is a sampling technique based on chance, namely who happens to meet the researcher can be used as a sample if deemed suitable. Based on the research results, each of the most influential variables is the empathy variable, then assurance, then followed by reliability, and responsiveness, while the lowest influential variable is tangible. Makassar Gapura Beach Hotel needs to maintain elements that have been rated well by customers and need to improve things that are still lacking.